Chemical and biological sensing using polarity of materials - Emge I.; Su C.; Sood R.; Arnold B.; Choa F.-S.; Kelly L.; Mandal K.D.; Verma M.K.; Singh N.B. (My University, 2025)
Polarity is very important in developing materials with colossal dielectric. To meet the demands for the tunable devices and high dielectric parallel plate capacitors, several perovskites such as CaCu3Ti4O12 (CCTO), La2/3Cu3Ti4O12 (LCTO) Pr2/3Cu3Ti4 O12 (PCTO) and several other materials of this class have been studied all over the world. Detailed studies showed that results vary a lot based on processing methods, such as powder vs. multi crystals and single crystals. In spite of great progress in processing, low resistivity and process driven variables in properties remain a big hurdle for its applications as a dielectric capacitor. We observed that dielectric values are significantly changed when these materials are exposed to chemicals and biological agents. We used parallel plate capacitor design for making chemical and biological sensors from CCTO member of this group. The data indicated huge difference in the dielectric and resistivity of the exposed samples. © 2020 SPIE.